Increased Anxiety-Related Behavior, Impaired Cognitive Function and Cellular Alterations in the Brain of Cend1-deficient Mice - Segklia, Katerina; Stamatakis, Antonios; Stylianopoulou, Fotini; Lavdas, Alexandros A.; Matsas, Rebecca (Frontiers in Cellular Neuroscience, 2019)
Cend1 is a neuronal-lineage specific modulator involved in coordination of cell cycle exit and differentiation of neuronal precursors. We have previously shown that Cend1−/− mice show alterations in cerebellar layering arising from increased proliferation of granule cell precursors, delayed radial granule cell migration and impaired Purkinje cell differentiation, leading to ataxic gait and deficits in motor coordination. To further characterize the effects of Cend1 genetic ablation we determined herein a range of behaviors, including anxiety and exploratory behavior in the elevated plus maze and open field, associative learning in fear conditioning, and spatial learning and memory in the Morris Water Maze. We observed significant deficits in all tests, suggesting structural and/or functional alterations in brain regions such as the cortex, amygdala and the hippocampus. In agreement with these findings, immunohistochemistry revealed reduced numbers of GABAergic interneurons in the adult cerebral cortex and the amygdala, most notably in the basolateral nucleus. The paucity in GABAergic interneurons in adult Cend1-/- mice correlated with increased proliferation and apoptosis as well as reduced migration of neuronal progenitors from the embryonic medial ganglionic eminence, the origin of these cells. Further we noted aberrant neurogenesis in the adult dentate gyrus of the hippocampus, which has been previously shown to confer spatial learning and memory deficits. Our data highlight the necessity of Cend1 expression in the formation of a structurally and functionally normal brain phenotype.